2012
DOI: 10.1590/s1413-70542012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antifungal activity of seaweed extracts

Abstract: Seaweeds are subject to numerous biological interactions and sometimes to extreme abiotic conditions, so they have developed among other defense mechanisms, the ability to produce biologically active substances. Thus, these organisms produce mainly terpenes and phenols. Among others, the antifungal activity, due to its importance in human and animal health and the production of agricultural products, has been the subject of several studies. In the present work, this activity was investigated in ten seaweeds ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 22 publications
1
22
2
5
Order By: Relevance
“…For example, some SWEs have bactericidal effects [18] associated with the presence of terpenes and phenolic compounds [17, 19]. Other reports indicate that seaweeds might stimulate the production of plant defense elicitors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some SWEs have bactericidal effects [18] associated with the presence of terpenes and phenolic compounds [17, 19]. Other reports indicate that seaweeds might stimulate the production of plant defense elicitors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Production of terpenes and phenols by some seaweed species has the potential to inhibit the growth of various fungal plant pathogens [50]. These bioactive polyphenol compounds, acting singly or in combination, interfere with the life process of fungi by binding their protein molecules, acting as chelating agents, altering structural component synthesis, weakening or destroying the permeability barrier of the cell membrane and changing the physiological status of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus niger showed resistance against majority of methanolic extracts. In Brazil, Peres, et al (2013) reported that ten seaweed extracts significantly inhibited the Colletotrichum lagenarium growth, but not inhibited significantly the Aspergillus flavus growth [13]. In Ireland, Rajauria and Abu-Ghannam (2013) screened antimicrobial activity and bioactive compounds of Himanthalia elongate (Brown Seaweed) [14].…”
Section: Journal Of Microbiology and Modern Techniquesmentioning
confidence: 99%